Local allergic rhinitis: Implications for management. Issue 1 (5th July 2018) - Campo, P.; Eguiluz‐Gracia, I.; Bogas, G.; Salas, M.; Plaza Serón, C.; Pérez, N.; Mayorga, C.; Torres, M. J.; Shamji, M.H.; Rondon, C.
Summary: A significant proportion of rhinitis patients without systemic IgE‐sensitisation tested by skin prick test and serum allergen‐specific IgE (sIgE) display nasal reactivity upon nasal allergen provocation test (NAPT). This disease phenotype has been termed local allergic rhinitis (LAR). LAR is an underdiagnosed entity affecting children and adults from different parts of the world, with moderate‐to‐severe symptoms, impairment of quality of life and rapid progression to symptom worsening. LAR is a stable phenotype and not merely an initial state of AR. Allergic rhinitis and LAR share many clinical features including a positive NAPT response, markers of type 2 nasal inflammation including sIgE in nasal secretions and a significant rate of asthma development. LAR should be considered as a differential diagnosis in those subjects of any age with symptoms suggestive of AR but no evidence of systemic atopy. Although LAR pathophysiology is partially unknown, in some patients sIgE can be demonstrated directly in the nasal secretions and/or indirectly via positive responses in basophil activation test (BAT). LAR can coexist with other rhinitis phenotypes, especially AR. The diagnosis currently relies on the positivity of NAPT to a single or multiple allergens. NAPT has high sensitivity, specificity and reproducibility, and it is considered the gold standard. BAT and the measurement of nasal sIgE can also contribute to LAR diagnosis. LAR patients benefit from the same therapeutic strategies than AR individuals, including the avoidance of allergen exposure and the pharmacotherapy. Moreover, several recent studies support the effectiveness and safety of allergen immunotherapy for LAR, which opens a window of treatment opportunity in these patients.